Produksi Hidrogen Secara Fotokalitik dari Air Murni Pada Katalis NaTaO3 - Husin, Husni (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2012)
Study of hydrogen production as a green energy on NaTaO3 photocatalyst has been done. The aim of this work is to study the photocatalytic properties of NaTaO3 and NiO incorporated NaTaO3 used in water splitting reaction. The NaTaO3 powder with high crystallinity has been synthesized by a H2O2-asissted sol-gel route calcined at a temperature of 900 oC. NiO as a cocatalyst is deposited by impregnation of Ni(NO3)2.6H2O solution. The catalysts are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM), and diffuse reflectance UV-Vis (DR-UV-Vis). The photocatalysts have a band gap energy ca. 4.01 and 4.00 eV (corresponding to absorption edge of 310 and 311 nm). Photocatalytic activity towards hydrogen generation from water is investigated using a glass reactor under ultra violet (UV) light illumination. Photocatalytic of H2 and O2 production on the pristine NaTaO3 are 0.61 and 0.30 mmol g-1 cat.h-1, respectively. The activities are greatly enhanced 8.5 times higher by the incorporation of NiO as cocatalysts on the prepared oxides. NiO is found to give rise to more efficient photocatalytic activity for hydrogen evolution. The NaTaO3 nanoparticles produces using this facile have: better crystallinity, smaller size, and higher photocatalytic activity.Keywords: Sodium tantalum oxide; Nickel oxide; Sol-gel; impregnation; Hydrogen evolution